SISTEM PENDETEKSIAN WAJAH PADA VIDEO MENGGUNAKAN JARINGAN ADAPTIVE LINEAR NEURON (ADALINE) - Fadlisyah Fadlisyah (Teknik Informatika Universitas Malikussaleh, 2013)
Face detection is an important first step to many advanced computer vision, biometrics recognition and multimedia applications, such as face tracking, face recognition, and video surveillance. In this paper, a faster face detection system is proposed using Adaptive Linear Neuron (ADALINE). System is constructed from the enhanced image by applying sobel operator, and then use the resulted image s vector to Widrow-Hoff learnings scheme. The performance of the proposed method is evaluated by two performances parameter, detection rate and false positive rate. The result shows that performance of detection rate is range from 65% to 90%. To enhance the quality of system performance, a combination of either : video complexity test, skin color segmentation, or statistical test, should be apllied to future research.